Respon Imun Larva Udang Vanamei (Litopenaeus vannamei) dengan Bioenkapsulasi Vitamin C pada Artemia salina - Ardiansyah, A; Rahmatia, R; Amrullah, A (Journal Galung Tropika, 2023)
The low quality of vannamei shrimp seeds during larval rearing causes vannamei shrimp seeds to be more susceptible to disease, thus affecting production success. This situation can be overcome by increasing the immune response of vanamei larvae through the administration of vitamin C. This study aims to evaluate the effectiveness of Artemia salina bio encapsulation with vitamin C to increase immunity against vibriosis disease of vannamei shrimp larvae. The treatment tried was the addition of vitamin C through A. salina bio encapsulation with four different doses, 20, 30, 40, and 50 ppm as well as control (without vitamin C), each with three replicates using a Completely Randomized Design (CRD). Vaname shrimp seeds were reared from Mysis-PL11 stadia in 50-liter capacity crates, 40-liter volume of media water with a density of 40 fish/liter, then checked Total hemocyte count (THC), Differential hemocyte count (DHC) before and after the challenge test was carried out by using Vibrio harveyii bacteria. The results showed that the effectiveness of the immunostimulant vitamin C through A. salina bio encapsulation to prevent vibriosis had a significant effect on the immune system of Mysis-PL11 stadia vannamei shrimp larvae with the highest THC value of 41 x 104 cells/mm, DHC (66.67% hyaline, 27 .67% semi-granular, 67.67% granular) in the treatment with the addition of 50 ppm vitamin C.